2012
DOI: 10.1155/2012/357040
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Inhibits Hedgehog Signaling and Induces Vitamin D Receptor Signaling and Differentiation in thePatchedMouse Model of Embryonal Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common soft tissue sarcoma in children. Aberrant Hedgehog (Hh) signaling is characteristic of the embryonal subtype (ERMS) and of fusion-negative alveolar RMS. In the mouse, ERMS-like tumors can be induced by mutations in the Hh receptor Patched1 (Ptch). As in humans these tumors show increased Hh pathway activity. Here we demonstrate that the treatment with the active form of vitamin D3, calcitriol, inhibits Hh signaling and proliferation of muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The treatment of the transfected cells was conducted in duplicates for each medium. Similar results were carried out after 4 and 8 h incubation of M2H-transfected NIH-3T3 cells with wt Ptch or Ptch ITZ Enhances the Antitumoral Potential of Calcitriol-Calcitriol efficiently inhibits Hh signaling and proliferation and stimulates differentiation processes in Ptch-associated cancers in mice (17,26). Moreover, the inhibitory effect of calcitriol on Hh signaling is still detectable when Hh signaling is constitutively activated due to the expression of the oncogene SMO-M2 (Fig.…”
Section: Calcitriol Efficiently Inhibits the Translocation Of Smo Intsupporting
confidence: 69%
See 3 more Smart Citations
“…The treatment of the transfected cells was conducted in duplicates for each medium. Similar results were carried out after 4 and 8 h incubation of M2H-transfected NIH-3T3 cells with wt Ptch or Ptch ITZ Enhances the Antitumoral Potential of Calcitriol-Calcitriol efficiently inhibits Hh signaling and proliferation and stimulates differentiation processes in Ptch-associated cancers in mice (17,26). Moreover, the inhibitory effect of calcitriol on Hh signaling is still detectable when Hh signaling is constitutively activated due to the expression of the oncogene SMO-M2 (Fig.…”
Section: Calcitriol Efficiently Inhibits the Translocation Of Smo Intsupporting
confidence: 69%
“…Recently we described that the oxysterol calcitriol, a twice hydroxylated vitamin D 3 derivative, efficiently inhibits Hh signaling of Ptch-associated tumors and Hh-stimulated wt Ptch and Ptch Ϫ/Ϫ cells (17,26). Moreover, we demonstrated that calcitriol inhibits Hh signaling downstream of Ptch but upstream of Gli supposedly at the level of Smo.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…39,116,118,134,135 These processes are regulated by cell-specific mechanisms and involve inhibition of hedgehog, β -catenin, NF κ B, and PI3K signaling pathways (refs 134,136,137 reviewed in refs 127,138). Apoptosis is also regulated by vitamin D. 1,25(OH) 2 D3-induced programmed cell death is mainly due to downregulation of the anti-apoptotic proteins Bcl-2 and Bcl-X L , upregulation of pro-apoptotic BAX, GOS2, DAP-3, FADD, and caspases (reviewed in refs 69,127,139).…”
Section: Vitamin D In a ‘Nutshell’mentioning
confidence: 99%